Development of Nata de Coco Product Marketing Strategy through Digital Marketing Pocket Book for Women Farmers Group in Pekik Nyaring Village - Serawai, Bembi Akbar; Fitri, Melani Anisa; Widiono, Septri; Azmi, Alia; Zubedi, Faradiba F (LPPM Universitas Jambi, 2026)
Pekik Nyaring Village is a village with abundant agricultural potential, especially coconut cultivation and agro-industry. In this village, the Women Farmers Group (KWT) plays a significant role in supporting the household economy through the production of coconut-based processed products, one of which is Nata de Coco. However, the resulting production faces challenges, namely limited marketing strategies. This community service aims to provide an understanding of digital marketing to the KWT. ​​The methods used in this activity are counseling and discussions targeting the women farmers group of Pekik Nyaring village. The digital marketing counseling activity for nata de coco products in the KWT of Pekik Nyaring village has had a positive impact, this condition is reflected in the enthusiasm of the KWT participants in implementing the activity. In addition, the results of the evaluation related to the understanding of the counseling material showed a 28% increase in knowledge and the KWT was able to create a digital platform as a digital marketing platform. This condition can be the foundation for the success of community service activities. Similar activities should continue to be carried out sustainably with several methods such as live demonstrations and mentoring. This is done to ensure sustainable change